Application of genetic algorithms to the evaluation of the fundamental frequency of stiffened plates - IWANIEC, M. (Archives of Acoustics, 2006)
In this paper, the analytical and numerical procedures for multi-stiffened plate free vibration analysis are presented. The plate and stiffeners are treated as an assembled plate and stiffening elements. The energy analysis leads to the nonlinear formulation of the non-dimensional frequency function formulated for a group of similar palates. The generalized optimization problem was solved by the use of the Nelder-Mead and genetic algorithms. The verification of the results obtained was performed on FEM models created for the same examples of the physical representation of the considered group of stiffened plates. This paper also aims the study of the influence of geometrical and material parameters of the stiffeners as well as the plate proportions on the fundamental frequency.